FACTORS RELATED TO CONSUMER SATISFACTION IN BUYING COFFEE AT A COFFEE SHOP (CASE STUDY : KOPI OM WARI, BIREUEN REGENCY, ACEH) - Fauzia, Lily; Fahira, Ila; Darus, Mozard Baharuddin; Jufri, Mohammad (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Coffee shops are popular destinations for Indonesians, not only for elders but also young people. Consumer satisfaction in buying coffee is one factor that needs to be analysed since it will have an impact on coffee shop sales. The objectives of this research is toanalyse the factors that are related to consumer satisfaction in purchasing coffee at Kopi Om Wari. The research location was at Kopi Om Wari since this coffee shop has a very large number of consumers and has survived for a long time despite other Coffee shops that were forced to close their businesses amid the many competitors that exist. The samples used were consumers who hadpurchased and visited Kopi Om Wari, with a total of 100 samples. The data analysis method used in this research uses the Spearman Rank Test. This research shows that Product Quality, Service Quality, Emotional, Price and Cost factors have a significant and positive relationship with consumer satisfaction.